2019
DOI: 10.1021/acs.jchemed.8b00874
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Importance of Laboratory Courses

Abstract: Laboratory courses are an ever-present form of teaching in chemistry, despite little evidence for their impact upon student learning. The chemistry community is challenged to consider the evidence basis for laboratory teaching commensurate with the significant investment of cost and time to provide this instruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
222
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(235 citation statements)
references
References 16 publications
3
222
0
10
Order By: Relevance
“…Experiments play a tremendous role in chemistry education, 1 but the impact of hands-on chemistry laboratories on students’ knowledge still requires research and better understanding. 2 During the COVID-19 pandemic outbreak and public lockout, all educators on all levels all over the world were challenged to conduct classes online. Chemistry/science school teachers were in a particularly tough situation because they had to organize teaching of not only theoretical knowledge but also practical aspects, and therefore, they needed to transfer experiments and laboratory activities to an online environment.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments play a tremendous role in chemistry education, 1 but the impact of hands-on chemistry laboratories on students’ knowledge still requires research and better understanding. 2 During the COVID-19 pandemic outbreak and public lockout, all educators on all levels all over the world were challenged to conduct classes online. Chemistry/science school teachers were in a particularly tough situation because they had to organize teaching of not only theoretical knowledge but also practical aspects, and therefore, they needed to transfer experiments and laboratory activities to an online environment.…”
Section: Introductionmentioning
confidence: 99%
“…Separately, we will stop at organizing laboratory classes in a remote format. As noted above, the specifics and peculiarities of chemical education in higher education dictate certain requirements for the implementation of experimental work [16,17]. Demonstration videos were selected for simpler works, for example, for laboratory classes to determine the heat of dissolution, neutralization, dissociation by calorimetry according to Physical Chemistry, for an experiment to obtain colloidal systems using various methods according to Colloidal Chemistry.…”
Section: Materials and The Results Of The Researchmentioning
confidence: 99%
“…This commitment is evident in the dedication of teaching resources, material, equipment, and specialized space to provide students with lab experiences. However, a recent survey of the literature by Bretz (2019) found no credible evidence to support that investment of resources. Furthermore, a direct experimental test by Holmes et al (2017) found no difference in outcomes on exam questions between students who had and had not experienced the lab as a conjugate to lecture.…”
Section: Opportunities and Challenges Of The Specific Stem Disciplinesmentioning
confidence: 97%